Spot Speed versus Speed Limit on Malaysian East-Coast Expressway - Sulistyo Arintono (JOURNAL OF SCIENCE AND APPLIED ENGINEERING, 2019)
Speed is one of the important causal factors for accidents on the road. This study aims to investigate the effectiveness of the speed warning sign on Malaysia’s East Coast Expressway where the rate of accident is high. Two points were selected, one representing locations far from any speed related warning sign, and one location immediately after a speed warning sign is in sight, to assess significance of the differences of the spot speeds. Results of the analysis suggest that the majority of vehicles (63.24%) travel over the speed limit, and that the speed warning sign does function in reducing the mean spot speed. However, the speed reduction is not to the desired level, i.e. under the speed limit. Other strategies have to be introduced to achieve the target.